Peripheral nerve regeneration and intraneural revascularization - Caillaud, Martial; Richard, Laurence; Vallat, Jean-Michel; Desmoulière, Alexis; Billet, Fabrice (Neural regeneration research, 2019)
Peripheral nerves are particularly vulnerable to injuries and are involved in numerous pathologies for which specific treatments are lacking. This review summarizes the pathophysiological features of the most common traumatic nerve injury in humans and the different animal models used in nerve regeneration studies. The current knowledge concerning Wallerian degeneration and nerve regrowth is then described. Finally, the involvement of intraneural vascularization in these processes is addressed. As intraneural vascularization has been poorly studied, histological experiments were carried out from rat sciatic nerves damaged by a glycerol injection. The results, taken together with the data from literature, suggest that revascularization plays an important role in peripheral nerve regeneration and must therefore be studied more carefully.